Assyrian Edition of Agathangelos - Sahakyan, Artsruni (Bulletin of Yerevan University B: Philology, 2022)
The Assyrian edition of Agathangelos was created by order of the Assyrian Church of the Akobikians during the Armenian-Assyrian church rapprochement on an anti-Chalcedonian basis when both churches under the rule of the Arab Caliphate were supposed to form a single anti-Byzantine religious front. The original was created immediately in the Assyrian language, without the Armenian original, on the basis of the Armenian-Greek written, as well as the Armenian oral sources. The article notes that the unknown Assyrian author probably had close ties with Bardzr Hayk, his spiritual, cultural, and ecclesiastical environment, as evidenced by his "local patriotism." The original was created in the calendar of the Akobikyan church. To perpetuate the memory of St. Gregory, around the 8th century (within 711-713).